Effect of Modulation on Throughput of 4G LTE Network Frequency 1800 MHz - Chandra, Dikky; Rahmat, Fauzi Aditia; Aulia, Siska; -, Firdaus; Kasmar, Andre Febrian (SOTVI, 2023)
In the development of 4G LTE technology, network speed (Throughput) in several regions has increased or decreased. Network speed (Throughput) certainly cannot be separated from Modulation.Â In modulation there are several kinds of modulation schemes, be it QPSK modulation, 16 QAM modulation, and 64 QAM modulation. The modulation scheme is instrumental in increasing throughput. Based on several previous studies, they only check the Throughput parameters without doing a more in-depth analysis of the modulation scheme which also plays a very important role in network speed (Throughput). For this reason, it is necessary to carry out an analysis related to the effect of modulation on the throughput value. To find out the effect of modulation on throughput, it is necessary to take data in the field, the method used is the Drive Test method. Based on the results of the Drive Test, QPSK modulation has a Throughput value of 5.247.4 Kbps, modulation of 16 QAM has a Throughput value of 27.293.9 Kbps and modulation of 64 QAM has a Throughput value of 65.275.1 Kbps. Based on the data in the field and in terms of calculations, the modulation that most affects the throughput value is the modulation of 64 QAM. Modulating 64 QAM having 64 symbols where each symbol consists of 6 bits will make the data rate at throughput higher. This also applies to the use of modulation of 16 QAM (16 symbols with 4 bits) and QPSK (4 symbols with 2 bits).